Analysis of the application of the think methodology, according to the “American Think Book”, in the 2nd year class “B” of Bachillerato General Unificado at “Combatientes de Tapi” high school in the city of Riobamba, during the first quimester school period 2017 – 2018 - Morocho Torres, Ambar Verenice (2018)
Through a previous analysis it was determined as a problem that student of the 2nd year class “B” of Bachillerato General Unificado at “Combatientes de Tapi” high school, it was observed that students are not highly compromised with their English performance improvement, due to the inappropriate development of “THiNK” methodology. This research analyses how THiNK methodology helps to enhance thinking and language skills. It was developed in the the 2nd year class “B” of Bachillerato General Unificado at “Combatientes de Tapi” High School in the city of Riobamba, during the first Quimester School period 2017 – 2018. The purpose of this research is to analyze how THiNK methodology helps to empower thinking skills and language skills, in order to enhance critical thinking in the students, it helps to develop critical thinking in the students to solve daily problems being conscious about the environment that surrounds them, through strategies synergy that combine thinking skills jointly with language skills development in order to improve English performance. The research was carried out with a population of 35 students, 25 of them boys and 20 girls. It is a qualitative research, of an exploratory scope and the qualitative method applied is ethnographic. It was used a non-participative observation technique due to the researcher plays a passive role, a tally sheet was used as a collecting data instrument. It was concluded that in the current academic year, THiNK methodology helps the students to develop the thinking critically capacity with language skills improvement, it has to be applied according the stablished process, paying attention at the moment of enhancing thinking skills and promoting progress in language skills development techniques.